A Note on the Accelerator and Constant Growth - Kervyn, A. (Review of Economic Studies, 1954)
Journal Article A Note on the Accelerator and Constant Growth Get access A. Kervyn A. Kervyn Geneva Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 1, 1954, Pages 61–66, https://doi.org/10.2307/2296225 Published: 01 January 1954